Comparison of single- and double-stage designs in the prevalence estimation of eating disorders in community samples - Labrador, Francisco Javier; Peláez-fernández, María Angeles; Raich, Rosa María (The Spanish Journal of Psychology, 2008)
The aim of this research was to compare two different case-identification designs: (a) a one-stage anonymous design using the Eating Disorders Examination-Questionnaire (EDE-Q; Fairburn & Beglin, 1994) as diagnostic instrument and (b) a two-stage-non-anonymous design using the Eating Attitudes Test (EAT; Garner & Garfinkel, 1979) and the EDE-Q as screening instruments and the clinical interview Eating Disorders Examination (EDE; Fairburn & Cooper, 1993) as diagnostic instrument, in the estimation of eating disorders prevalence in community samples. Both epidemiological designs were compared in: eating disorders prevalence, population at risk, and weekly frequency of associated symptomatology (binge eating episodes, self-vomiting) within a sample of 559 scholars (14 to 18 year-old males and females) studying in the region of Madrid. Eating disorders prevalence estimation using single-stage design was 6.2%, and 3% using the two-stage design; however, these differences were not significant (p = .067). No significant differences between the two procedures were found either in population at risk or in weekly frequency of reported self-vomiting. Reported binge eating episodes were higher in the one-stage design. The use of a two-stage procedure with clinical interview (vs. questionnaire) leads to a better understanding of the items (specially the most ambiguous ones) and thus, to a more accurate prevalence estimation.